2017
DOI: 10.1371/journal.pone.0177824
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of spontaneously contracting cardiomyocytes from non-virally reprogrammed human amniotic fluid stem cells

Abstract: Congenital heart defects are the most common birth defect. The limiting factor in tissue engineering repair strategies is an autologous source of functional cardiomyocytes. Amniotic fluid contains an ideal cell source for prenatal harvest and use in correction of congenital heart defects. This study aims to investigate the potential of amniotic fluid-derived stem cells (AFSC) to undergo non-viral reprogramming into induced pluripotent stem cells (iPSC) followed by growth-factor-free differentiation into functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
2
21
0
Order By: Relevance
“…Hence, the quest is now on defining the most suitable cell to efficiently induce iPS from and since amniotic fluid stem cells are immature fetal progenitors endowed with some degree of instrinsic pluripotency and active expression of embryonic genes including OCT4, NANOG, and SOX2 (Loukogeorgakis and De Coppi, 2017 ), they represent an ideal candidate. Recent studies have reported that murine and human AFSC can be reprogrammed into iPS more easily than adult stem cells by applying either transgene-free approaches, like chemical defined conditions via stimulation with the histone deacetylase inhibitor valproic acid (Moschidou et al, 1953 ), as well as non-integrating methods by episomal plasmid, transposon system, sendai virus or mRNA delivery by lipofection (Jiang et al, 2016 ; Slamecka et al, 2016 ; Bertin et al, 2017 ; Velasquez-Mao et al, 2017 ); notably the obtained AFSC-iPS have been proven capable of functional cardiac differentiation, thus providing important impact for future cardiac regenerative therapy and specific relevance for the treatment of neonatal cardiac congenital disease (Jiang et al, 2016 ; Velasquez-Mao et al, 2017 ). Indeed, hAFSC can be effortlessly harvested during prenatal diagnosis, treated by gene therapy and iPS technology to derived healthy myocardial and cardiovascular cells to be then processed by tissue engineering approaches so to provide cardiac grafts developed in parallel with gestation and promptly implanted in utero or at birth.…”
Section: Fetal Progenitors: Amniotic Fluid Stem Cells For Cardiac Repmentioning
confidence: 99%
“…Hence, the quest is now on defining the most suitable cell to efficiently induce iPS from and since amniotic fluid stem cells are immature fetal progenitors endowed with some degree of instrinsic pluripotency and active expression of embryonic genes including OCT4, NANOG, and SOX2 (Loukogeorgakis and De Coppi, 2017 ), they represent an ideal candidate. Recent studies have reported that murine and human AFSC can be reprogrammed into iPS more easily than adult stem cells by applying either transgene-free approaches, like chemical defined conditions via stimulation with the histone deacetylase inhibitor valproic acid (Moschidou et al, 1953 ), as well as non-integrating methods by episomal plasmid, transposon system, sendai virus or mRNA delivery by lipofection (Jiang et al, 2016 ; Slamecka et al, 2016 ; Bertin et al, 2017 ; Velasquez-Mao et al, 2017 ); notably the obtained AFSC-iPS have been proven capable of functional cardiac differentiation, thus providing important impact for future cardiac regenerative therapy and specific relevance for the treatment of neonatal cardiac congenital disease (Jiang et al, 2016 ; Velasquez-Mao et al, 2017 ). Indeed, hAFSC can be effortlessly harvested during prenatal diagnosis, treated by gene therapy and iPS technology to derived healthy myocardial and cardiovascular cells to be then processed by tissue engineering approaches so to provide cardiac grafts developed in parallel with gestation and promptly implanted in utero or at birth.…”
Section: Fetal Progenitors: Amniotic Fluid Stem Cells For Cardiac Repmentioning
confidence: 99%
“…In this regard, one study provides compelling evidence on the possibility to generate a population of beating amniotic fluid-derived cardiomyocytes (AF-CMs) after Sendai virus reprogramming towards pluripotency [45]. Similar data were confirmed by other groups that have focused their attention on possibility to obtain functional cardiomyocytes from iPSC reprogramming using nonviral methods [46]. Taken together, these findings provide evidences that amniotic fluid (AF) could represent an ideal source for autologous cells for the treatment of neonatal congenital heart defects and neurodegenerative diseases.…”
Section: Epigenetic Changes In Afsc Reprogrammingmentioning
confidence: 76%
“…More recently, the differentiation of cells from autologous amniotic fluid iPSCs into functional cardiomyocytes by integration‐free reprogramming methods has also been demonstrated (Fig. ) . Amniotic fluid‐derived stem cells are likely to play an additional role as paracrine mediators of tissue regeneration based on experimental models of adult heart disease .…”
Section: Selected Congenital Anomalies Amenable To Amniotic Fluid Stementioning
confidence: 99%